Towards a multi-lateral framework for cross-border surveillance and information sharing between Nigeria and neighbouring countries - Chinenye Ofoegbunam; Virgil Lokossou; Olaoluwa Oluwafemi Akinloluwa; Geoffrey Okatubo; Oyeladun Okunromade; Onyekachi Nwitte-Eze; Samuel Alabi; Titilope Ajayi-Ogbe; Lionel Sogbossi; Kima Appolinaire; Melchior Anathase Aissi (BMJ Global Health)
Nigeria sits at the crossroads of West and Central Africa; two increasingly critical regions for global health security. To strengthen cross-border collaboration for health security between its neighbors from West and Central Africa, the Federal Ministry of Health, Nigeria through the public health authority at the Points of Entry—Port Health Services, led the design of a multi-lateral framework for cross-border collaboration between Nigeria, the Republic of Benin, the Republic of Chad, the Republic of Cameroon and the Republic of Niger. This framework provides a platform for agreeing on bilateral national and district-level infectious disease surveillance information sharing as well as laying the groundwork for expanded collaboration in incident reporting, joint investigation and response across borders.